Metode Ijtihad Komisi Fatwa Majelis Ulama Indonesia dan Aplikasinya dalam Fatwa - Heri Fadli Wahyudi; Fajar Fajar (Universitas Muhammadiyah Magelang, 2018)
Al-Quran and Hadits as main sources of Islamic law are of a limit in numbers, yet the emerging matters in life are complex and limitless. In order to face problems which are more complicated and fuller of novelty, sometimes there is no specific law on the matters in Al-Quran and Hadits, thus ijtihad is necessary for this situation. One of the reasons in the formation of the Indonesian Ulama Council (MUI) is to respond and answer many religious matters emerging within society. As an Islamic community-shading institution with authority to issue a fatwa, MUI must have a method in performing ijtihad. Based on that reality, this paper seeks to explore the MUI-used ijtihad method and its implementation in the fatwa issue. This research found that the ijtihad method of MUI uses three approaches; Nash Qath’i approach, Qauli approach, and Manhaji approach based on its contexts